Gender and tenure predict Filipino science teachers’ instrumentation skills - Linaugo, Joji D. (Edelweiss Applied Science and Technology, 2025)
Instrumentation skills coupled with appropriate pedagogical skills are important in the science classroom. This study examined the instrumentation skills of science teachers from public urban schools representing the three major island groups in the Philippines. Using post-positivist descriptive-correlational survey research, a total of 200 science teachers served as the respondents of this study. A valid (CVI=0.83) and reliable (α=0.98) researcher-made instrument was used to gather data. Stepwise multiple linear regression was used to analyze the data. The results suggest that gender and tenure are significant predictors of instrumentation skills among secondary science teachers. Workshops emphasizing practical hands-on experiences, focusing on female teachers who have stayed longer in the service, are recommended.